3D Printed Swordfish‐Like Wireless Millirobot - Xingcheng Ou; Yu Sheng; Jiaqi Huang; Dantong Huang; Xiaohong Li; Ran Bi; Guoliang Chen; Weijie Hu; Shuang‐Zhuang Guo (Advanced Intelligent Systems)
Inspired by the efficient swimming capabilities of swordfish, a novel wireless soft swordfish‐like robot with programmable magnetization has been developed, integrating direct‐ink‐writing (DIW) 3D printing and assembly technology. This 20 mm long robot features a streamlined form and magnetically programmable movements, enabling biomimetic locomotion patterns such as straight‐line swimming and turning swimming. The robot includes a silicone‐based torso (body, abdomen, and pectoral fin) and a crescent‐shaped tail fin made from a magnetically programmable polymer embedded with neodymium‐iron‐boron (NdFeB) particles. The tail fin, fabricated by multi‐material alternating printing to achieve a gradient magnetism distribution, is controlled by an external magnetic field to mimic the rapid oscillation of a swordfish's tail, achieving a swimming speed of 0.51 BL/ s. The tail fin's asymmetric oscillation amplitudes, adjusted by magnetic field control, allow the robot to transition seamlessly from high‐speed straight swimming to agile turning. The robot can perform tracking swimming along specific planned paths, such as “C” and “Z” shaped trajectories. Potential applications include environmental monitoring and targeted drug release. The multi‐material 3D printing technology enhances the robot's efficiency and sensitivity in simulating natural biological movements, extending to the design and development of various flexible devices and soft robots.